2020
DOI: 10.7554/elife.59099
|View full text |Cite
|
Sign up to set email alerts
|

The autophagy adaptor NDP52 and the FIP200 coiled-coil allosterically activate ULK1 complex membrane recruitment

Abstract: The selective autophagy pathways of xenophagy and mitophagy are initiated when the adaptor NDP52 recruits the ULK1 complex to autophagic cargo. Hydrogen-deuterium exchange coupled to mass spectrometry (HDX-MS) was used to map the membrane and NDP52 binding sites of the ULK1 complex to unique regions of the coiled coil of the FIP200 subunit. Electron microscopy of the full-length ULK1 complex shows that the FIP200 coiled coil projects away from the crescent-shaped FIP200 N-terminal domain dimer. NDP52 allosteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 43 publications
3
47
0
Order By: Relevance
“…The addition of NDP52 or TAX1BP1-Ub, with GST-Ub4, dramatically enhanced the membrane binding of ULK1 complex (Fig. 4A, second and third columns, B, and C), consistent with the previous observations that NDP52 directly recruited ULK1 complex in mitophagy or xenophagy (28)(29)(30). We noticed that only a little LC3 lipidation occurred even though the ULK1 complex was enriched on the membrane upon the addition of GST-Ub4 with either NDP52 or TAX1BP1 (Fig.…”
Section: Kinetics Of Ulk1 Complex Recruitment To Membranessupporting
confidence: 90%
See 4 more Smart Citations
“…The addition of NDP52 or TAX1BP1-Ub, with GST-Ub4, dramatically enhanced the membrane binding of ULK1 complex (Fig. 4A, second and third columns, B, and C), consistent with the previous observations that NDP52 directly recruited ULK1 complex in mitophagy or xenophagy (28)(29)(30). We noticed that only a little LC3 lipidation occurred even though the ULK1 complex was enriched on the membrane upon the addition of GST-Ub4 with either NDP52 or TAX1BP1 (Fig.…”
Section: Kinetics Of Ulk1 Complex Recruitment To Membranessupporting
confidence: 90%
“…Negative stain electron microscopy (NSEM) images showed that FIP200 Δ641-779 had essentially the same structure as wild-type, while losing its propensity to aggregate (fig. S2C) ( 29 ). Contour lengths and end-to-end distances of FIP200 Δ641-779 as analyzed by NSEM were comparable as the full-length (fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations